2008
DOI: 10.1088/1475-7516/2008/06/033
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic structures via Bose–Einstein condensation and its collapse

Abstract: We develop our novel model of cosmology based on the Bose-Einstein condensation. This model unifies the Dark Energy and the Dark Matter, and predicts multiple collapse of condensation, followed by the final acceleration regime of cosmic expansion. We first explore the generality of this model, especially the constraints on the boson mass and condensation conditions. We further argue the robustness of this model over the wide range of parameters of mass, self coupling constant and the condensation rate. Then th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 16 publications
5
95
0
Order By: Relevance
“…This has lead some to general consideration of Bose-Einstein-Condensate (BEC) dark matter (see, for example, [47][48][49], and in the case of axions [50,51]). Indeed, the numerical simulation of [52] showed that the presence of such an ultra-light scalar condensate indeed reduces the number of dwarf galaxies, but in fact does very little to the cuspy density profile.…”
mentioning
confidence: 99%
“…This has lead some to general consideration of Bose-Einstein-Condensate (BEC) dark matter (see, for example, [47][48][49], and in the case of axions [50,51]). Indeed, the numerical simulation of [52] showed that the presence of such an ultra-light scalar condensate indeed reduces the number of dwarf galaxies, but in fact does very little to the cuspy density profile.…”
mentioning
confidence: 99%
“…Imposing this thermodynamic condition on Eqs. (18) and (30) helps us to fix the transition density ρ cr χ as follows:…”
Section: Cosmological Parameters At the Condensation Pointmentioning
confidence: 99%
“…Based on the above arguments, we assume the possibility that the Bose-Einstein condensation might have happened during the early stages of cosmological evolution of the universe with a temperature comparable to the critical temperature for Bose-Einstein condensation T cr ∼ 2πh 2 n 2/3 /mk B where m is the particle mass, n is the particle density, and k B is Boltzmann's constant [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium properties of Newtonian self-gravitating Bose-Einstein condensates with short-range interactions were investigated in detail in [35,36]. The study of the cosmological implications of the Bose-Einstein condensation has also become an active field of research [37][38][39][40][41][42][43][44][45][46]. In particular, in [44] it was shown that condensate dark matter effects can be seen in the CMB matter power spectrum if the mass m χ of the condensate particle lies in the range 15 meV < m χ < 700 meV, leading to a small, but perceptible, excess of power at large scales.…”
Section: Introductionmentioning
confidence: 99%